PENGAMANAN TEKS MENGGUNAKAN ALGORITMA TRANSPOSISI DAN MODIFIKASI SANDI MORSE - Rizki Gangsar Septiono; Kiswara Agung Santoso; Ahmad Kamsyakawuni (UNEJ e-Proceeding, 2022)
Humans as social beings communicate to exchange information. Information has many forms including text data, sound, images, and so on. Not all information is freely accessible. Information security is needed to prevent information from being misused by irresponsible parties. Cryptography studies how to convert information into a form that is unknown except for the sender and recipient of the information. Cryptography is divided into two, classical cryptography and modern cryptography. One form of cryptography that can be found around us is the use of Morse code in scouting. Classical cryptography and modern cryptography can be combined to increase the security of the algorithms used in hiding information. In this article, the transposition algorithm is applied in binary digits. Keys in the form of ASCII characters are converted into binary using modified Morse code and operated with plaintext. The results showed that the combination of transposition algorithm and Morse code modification adds complexity so that the proposed algorithm is difficult for cryptanalysts to solve. Keywords: Cryptography, Morse Code, Transposition Algorithm.